HOW TO THINK ABOUT THE GUN CONTROL DEBATE. Issue 52 (2019) - Hsiao, Timothy
Abstract : Many on both sides of the gun control debate are under the impression that the best way to settle it is by weighing outcomes in the context of a utilitarian cost-benefit analysis. This article suggests that this way of thinking about the gun control debate is fundamentally mistaken. What matters is not the risk (or lack thereof) that guns pose to society, but simply whether guns are a reasonable means of self-defence when used to resist crimes. What this means is that even if we were to grant the claim that gun ownership decreases average safety, it wouldn't follow that restrictive gun control measures would be justified.